2021
DOI: 10.21037/jtd-21-229
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic sympathetic block to predict compensatory hyperhidrosis in primary hyperhidrosis

Abstract: Background: Compensatory hyperhidrosis is the main cause of patients' dissatisfaction following sympathectomy for primary hyperhidrosis. Therefore, thoracoscopic sympathetic nerve block before sympathectomy can be used to predict compensatory hyperhidrosis after sympathectomy. The objective of this study is to review our recent experience with the nerve block procedure, describing efficacy, safety and validity.Methods: We retrospectively reviewed the medical records of 107 patients who underwent thoracoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Sun and his colleagues reported that high thoracic sympathetic block improved myocardial capillary spasm and growth. TSNB can also be applied as a predictive procedure for compensatory hyperhidrosis before sympathectomy in primary hyperhidrosis, based on the effect of sympathetic block on increasing skin perfusion and temperature through vasodilation at the anesthetized sites (10,11,19,20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sun and his colleagues reported that high thoracic sympathetic block improved myocardial capillary spasm and growth. TSNB can also be applied as a predictive procedure for compensatory hyperhidrosis before sympathectomy in primary hyperhidrosis, based on the effect of sympathetic block on increasing skin perfusion and temperature through vasodilation at the anesthetized sites (10,11,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, there have been several approaches to blocking thoracic sympathetic nerve: the landmark-based approach, US-guided approach, CT-guided approach, uoroscopically, and thoracoscopically (10)(11)(12)(13)(21)(22)(23). A classic technique that does not use image guidance is a landmarkbased approach that elicits a loss of resistance (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this goal in mind, Lee et al in the past 10 years developed a procedure to obtain a temporary nerve block to simulate definitive sympathectomy and predict after surgery outcomes of patient (23). In particular, they introduced a thoracoscopic sympathetic block under local anesthesia.…”
Section: Temporary Thoracoscopic Sympathetic Block Techniquementioning
confidence: 99%